Optogenetic control of body movements via flexible vertical light-emitting diodes on brain surface. (February 2018) - Lee, Seung Hyun; Kim, Jeongjin; Shin, Jung Ho; Lee, Han Eol; Kang, Il-Suk; Gwak, Kiuk; Kim, Dae-Shik; Kim, Daesoo; Lee, Keon Jae
Abstract: The microstimulation of specific neural populations of the brain is one of the facile and reliable methods used in neuroscience for deduction of functional movement, complex behavior and even long-range connectivity. Recent advanced biomedical tools now employ flexible optoelectronic devices combined with optogenetic mouse models to induce high spatiotemporal modulation of specific brain activity. However, most current applications are limited to activation of small functional regions using blue-light driven channelrhodopsin. In this report, we introduce flexible AlGaInP vertical light-emitting diodes (VLEDs) for perturbation of specific functional areas of mouse cortex. Micro-scaled LEDs effectively compress the conductive balls dispersed in anisotropic conductive film (ACF) resulting red light emissions with high optical power density, capable of stimulating motor neurons deep below layer III from the brain surface. Selective operation of pulsed red light from f-VLEDs induces mouse body movements and synchronized electromyogram (EMG) signals. The expression of chrimson, red-shifted channelrhodopsin, enables red-light excitation of targeted functional area of motor cortex. This demonstration opens new opportunities for entire cortical mapping, to explore the connectivity between undefined motor areas in the mouse brain. Graphical abstract: Highlights: The flexible vertical light-emitting diodes (f-VLEDs) were fabricated by an anisotropic conductive film (ACF). The f-VLEDs showed the optical power density more than 25 mW/mm 2, enough to stimulate the motor neurons below layer III. The f-VLEDs illuminated the frontal motor cortex of the mouse to control the body movements with minimal tissue damage.